Oil-Type Sunflower Cost-Return Budget in North Central and Northeast Kansas - Lubben, Bradley D. (My University, 2000)
This publication provides estimated cost and returns for forward farm planning for producing sunflowers in north central and northeastern Kansas.
MF2144_2000_10
Keywords: MF2144; Crops; Economics; MF